A Qualitative Study on Formal and Informal Carers' Perceptions of Dementia Care Provision and Management in Malaysia - Goodson, Michaela; McLellan, Emma; Rosli, Roshaslina; Tan, Maw Pin; Kamaruzzaman, Shahrul; Robinson, Louise; Moloney, Susan (Frontiers in Public Health, 2021)
Background: The number of people living with dementia worldwide is increasing, particularly in low- and middle-income countries (LMICs) where little is known about existing post-diagnostic care and support. This study aimed to better understand healthcare provision for people living with dementia in Malaysia, and to identify priorities for providing timely, quality, and accessible care and support to all. Methods: This is a qualitative interview study on care providers and facilitators (health and community care professionals, paid carers, traditional medicine practitioners, faith healers, community leaders, non-governmental organisations). A topic guide, piloted in Malaysia and peer reviewed by all LMIC partners, elicited the understanding of dementia and dementia care and barriers and facilitators to care for people living with dementia and carers, and perceptions of key priorities for developing efficient, feasible, and sustainable dementia care pathways. Verbatim transcription of audio-recorded interviews was followed by iterative, thematic data analysis. Results: Twenty interviews were conducted (11 healthcare professionals, 4 traditional medicine practitioners, and 5 social support providers). The findings indicate that dementia care and support services exist in Malaysia, but that they are not fully utilised because of variations in infrastructure and facilities across the country. Despite a locally recognised pathway of care being available in an urban area, people with dementia still present to the healthcare system with advanced disease. The interviewees linked this to a public perception that symptoms of dementia, in particular, are normal sequelae of ageing. Earlier detection of dementia is commonly opportunistic when patients present to GPs, government clinic staff, and general physicians with other ailments. Dementia may only be identified by practitioners who have some specialist interest or expertise in it. Workforce factors that hindered early identification and management of dementia included lack of specialists, overburdened clinics, and limited knowledge of dementia and training in guideline use. Post-diagnostic social care was reported to be largely the domain of families, but additional community-based support was reported to be available in some areas. Raising awareness for both the public and medical professionals, prevention, and more support from the government are seen as key priorities to improve dementia management. Conclusions: This qualitative study provides novel insight into the availability, delivery, and use of post-diagnostic care and support in Malaysia from the perspective of care providers. The respondents in this study perceived that while there was a provision for dementia care in the hospital and community settings, the different care sectors are largely unaware of the services each provides. Future work should explore how care provision across different service sectors and providers can be supported to better facilitate patient access and referral between primary, secondary, and social care. The importance of supporting families to understand dementia and its progression, and strategies to help them care for relatives was emphasised. There is also a need for broad workforce training and development, at both the postgraduate and undergraduate levels, as well as improved general awareness in the community to encourage earlier help-seeking for symptoms of dementia. This will enable the use of preventive strategies and access to specialist services to optimise care and quality of life for people living with dementia in Malaysia.